How companies are securing their supply chain during crisis situations - Honkanen, Urho (Hämeen ammattikorkeakoulu, 2013)
ABSTRACT The economic environment has been challenging for global companies for many years. In addition to this, there has been large natural disaster such as the tsunami in Japan, flooding in Thailand and Iceland volcanic eruption. All of these things have contributed to the global industry, especially for the availability of raw materials or components. Thus, to identify, assess, manage risks and to inform their effects as early as possible has become increasingly important in risk management. The aim of this research was to examine how different companies ensure the continuity of production and the availability of the material in case of crisis situations. The study is primary based on the theory and secondly on interviews that were made to companies which are functioning in a global environment. The interviewed companies are not restricted to any particular category. The study was conducted with semi-structured theme interviews. Subject of the study was divided into two categories; how to ensure own production, as well as how to ensure supplier’s production in supply chain from risk management point of view. There are clear differences between companies in ensuring of production and availability of the material levels. However, each company chooses its own risk management level. Only, in a few companies there were clear challenges to understand how this should be done and what it means in practice. In general, companies didn't take enough notice of vulnerability of their IT-systems. In many cases managing the IT-systems was outsourced and the company itself didn’t know how IT systems are ensured. However, all the business actions are based on availability of the IT-systems and utilizing of data. Due to a few days of interruption or loss of data can cause substantial losses and costs to company. This would be an area where many companies should particularly focus at. TIIVISTELMÄ Taloudellinen tilanne on ollut globaaleille yrityksille haastava jo vuosia. Lisäksi on ollut mullistavia luonnon katastrofeja ...